Systematic review of sustainable urban community development trends challenges and opportunities - Yafeng Lai; Pohsun Wang; Jun Xia (Discover Sustainability)
Abstract The continuous growth of the global urban population has exerted immense pressure on environmental, social, and economic systems, compelling greater attention to the sustainable development of cities and their communities. This study conducted a bibliometric analysis of 417 articles from the Web of Science Core Collection, systematically summarizing the key trends, challenges, and opportunities in the field of sustainable urban community development. It also sheds light on the evolution of research hotspots and academic priorities. The findings indicate that the sustainable development of urban communities has become a global focal point. Future research will likely focus on smart city technologies, the application of artificial intelligence, community participation, and social equity, which are critical topics that will drive research and practice in the coming years. Interdisciplinary collaboration integrating knowledge from environmental science, sociology, economics, and other fields is crucial for achieving sustainable urban community development. This study contributes by providing a comprehensive overview of the progress made in research on sustainable urban communities from multiple perspectives. It not only identifies future research directions, focusing on the synergy between technological innovation and community participation, but also offers practical recommendations for policy-makers. These recommendations will help align technological advancements with community needs, ultimately fostering more equitable and sustainable urban communities.